2015
DOI: 10.1177/1535370215592122
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium of sortase A dimerization on Staphylococcus aureus cell surface mediates its cell wall sorting activity

Abstract: Staphylococcus aureus sortase A (SrtA) transpeptidase is a therapeutically important membrane-bound enzyme in Gram-positive bacteria, which organizes the covalently attached cell surface proteins on the peptidoglycan cell wall of the organism. Here, we report the direct observation of the highly selective homo-dimerization of SrtA on the cell membrane. To address the biological significance of the dimerization towards enzyme function, site-directed mutagenesis was performed to generate a SrtA mutant, which exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…(ii) The active site is predominantly defined by the intrinsic flexibility of the β6/7‐ and β7/8‐loops . (iii) The most active form of SrtA is constituted as a homo‐dimer with a K D =55 μM . (iv) The K M values for both, the LPXTG‐ and Gly n ‐substrates are exceptionally high ( K M = 5.5 mM and 0.14 mM), probably due to the fact that the enzyme and both substrates are spatially co‐localized at the outer membrane yielding high local concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The active site is predominantly defined by the intrinsic flexibility of the β6/7‐ and β7/8‐loops . (iii) The most active form of SrtA is constituted as a homo‐dimer with a K D =55 μM . (iv) The K M values for both, the LPXTG‐ and Gly n ‐substrates are exceptionally high ( K M = 5.5 mM and 0.14 mM), probably due to the fact that the enzyme and both substrates are spatially co‐localized at the outer membrane yielding high local concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…Sortase A of S. aureus (SaSrtA) has been shown to exist in a monomerdimer equilibrium in solution [42]. However, functional evaluation of individual species of SaSrtA produced curious results [45]; while in vitro studies showed increased enzyme . Each dimer contains two characteristic 8-stranded beta barrel "sortase fold", but each fold in the dimer is constituted by the combination of beta-strands from both the chains, that is, a complete fold is made through 3D-swapping.…”
Section: Discussionmentioning
confidence: 99%
“…Surface proteins at the leucineproline-variable amino acid(X)-threonine-glycine (LPXTG) can be cleaved by Srt and the formation of an amide bond between the carboxyl group of threonine(T) and the amino group of cell-wall cross-bridges (Siegel et al, 2017). The deficiency of srtA in S. aureus severely impedes the anchoring of bacterial surface proteins, thereby significantly reducing their adherence and invasion of host epithelial cells resulting in reduced virulence (Zhu et al, 2016).…”
Section: Sortase(srt)mentioning
confidence: 99%